Andesites and evolution of the continental crust: Perspectives from the Central Volcanic Zone of the Andes - Burns, Dale H.; de Silva, Shanaka L. (Frontiers in Earth Science, 2023)
Named for the Andes, andesites (53%–63% SiO2) are the archetypal magma erupted at magmatic arcs. They have been established as the average composition of continental crust and as such are integral to the growth and evolution of the continental crust. However, andesites are quite variable in trace element and isotopic composition reflecting disparate paths of origin. Herein we return to the original site of their identification, the Central Andes, and use a comprehensive dataset of published and unpublished trace elements and isotopes to show that during the past 6 Myr two distinct types of andesite have erupted in the Central Volcanic Zone (CVZ), which correspond with different geodynamic conditions. Consistent with previous work, we confirm that major composite cones and minor centers of the steady state (low magmatic flux) Quaternary CVZ arc have trace element and isotopic characteristics consistent with magma generation/fractionation in the lower crust. Within the Quaternary arc centers, there are also significant latitudinal variations that correspond with the age, composition, and P-T conditions of the lower crust. However, in contrast to this prevailing model, in the 21–24°S segment 6–1 Ma andesites from ignimbrites and lava domes associated with the peak of the regional Neogene ignimbrite flare-up have compositions that indicate these andesites are hybrids between mantle-derived basalts and upper crustal lithologies. Since ∼1 Ma, andesites in young silicic lava domes associated with the regional flare-up are compositionally indistinguishable from proximal Quaternary arc centers, indicating a return to steady-state magmatism and lower crustal production of andesites. We propose that the transition from upper crustal to lower crustal andesite production results from a decrease in mantle heat input and subsequent relaxation of the regional geotherm during the waning of the flare-up event. The two modes of andesite production have significant implications for the production and evolution of the CVZ arc crust. During the flare-up, prodigious amounts of basalt were emplaced into the mid-crust, resulting in the production of large volumes of hybrid intermediate magmas in the mid and upper crust. In contrast, the lower crustal differentiation recorded in the Quaternary steady state arc andesites would result in the formation of a dense crystalline residue in the lower crust and an overall densification of the lower crust. Over time, gravity instabilities associated with this densification may ultimately aid in the delamination of the dense lower crustal root, triggering flare-ups. These differences in andesite production may help explain the cyclicity (flare-up cycles) observed in mature continental arcs and emphasizes that andesite is not a monotonous composition and can vary with depth-dependent intra-crustal differentiation related to magmatic flux.